2021
DOI: 10.3390/pharmaceutics13071095
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oral Treatment with Non-Hypoglycemic Dose of Glibenclamide Reduces Diabetic Retinopathy Damage in the Goto-KakizakiRat Model

Abstract: Diabetic retinopathy (DR) remains a major cause of vision loss, due to macular edema, retinal ischemia and death of retinal neurons. We previously demonstrated that acute administration of glibenclamide into the vitreous, or given orally at a non-hypoglycemic dose, protected the structure and the function of the retina in three animal models that each mimic aspects of diabetic retinopathy in humans. In this pilot study, we investigated whether one year of chronic oral glibenclamide, in a non-hypoglycemic regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…84 • The ABCC8 encoded SUR-1 protein is crucial in retinal function and SU (glibenclamide) confers direct retinal neuroprotection through SUR-1 mediated mechanisms. 85,86 • A recent study utilized patient-derived iPSCs to generate cerebral organoids and found major defects in early development of cortical neuronal network in V59M mutants compared to controls, that could partially be rescued by the SU tolbutamide. 87 Activating mutations in KCNJ11 causing NDM are always heterozygous.…”
Section: Permanent Neonatal Diabetes Due To Mutations In the K Atp Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…84 • The ABCC8 encoded SUR-1 protein is crucial in retinal function and SU (glibenclamide) confers direct retinal neuroprotection through SUR-1 mediated mechanisms. 85,86 • A recent study utilized patient-derived iPSCs to generate cerebral organoids and found major defects in early development of cortical neuronal network in V59M mutants compared to controls, that could partially be rescued by the SU tolbutamide. 87 Activating mutations in KCNJ11 causing NDM are always heterozygous.…”
Section: Permanent Neonatal Diabetes Due To Mutations In the K Atp Ch...mentioning
confidence: 99%
“…However, those with PNDM due to ABCC8 mutations had a similar range of difficulties as those with PNDM due to KCNJ11 mutations 84 The ABCC8 encoded SUR‐1 protein is crucial in retinal function and SU (glibenclamide) confers direct retinal neuroprotection through SUR‐1 mediated mechanisms 85,86 A recent study utilized patient‐derived iPSCs to generate cerebral organoids and found major defects in early development of cortical neuronal network in V59M mutants compared to controls, that could partially be rescued by the SU tolbutamide 87 …”
Section: Specific Subtypes Of Monogenic Diabetes and Their Managementmentioning
confidence: 99%
“…48 Studies of effects on retinal function support these possibilities: low-dose oral glibenclamide failed to significantly lower Hb1Ac levels yet decreased retinal-cell death and improved retinal function. 57,58 Our subgroup analysis suggests that age at sulfonylurea initiation may be strongly associated with the likelihood of benefits. Thus, neurological improvements were more likely when the treatment was started before 4 years of age, in keeping with the greater neuronal plasticity in younger individuals.…”
Section: Discussionmentioning
confidence: 88%
“…Sulfonylureas may also decrease vasogenic cerebral oedema and cerebral inflammation, thereby promoting the reperfusion of ischaemic areas 48 . Studies of effects on retinal function support these possibilities: low‐dose oral glibenclamide failed to significantly lower Hb1Ac levels yet decreased retinal‐cell death and improved retinal function 57,58 …”
Section: Discussionmentioning
confidence: 99%
“…Of note, the medical use of glibenclamide is associated with the risk of hypoglycemia in diabetic and non-diabetic patients (Soydan et al 2013 ). However, the use of a non-hypoglycemic dose of glibenclamide 0.4 mg/kg still has an anti-inflammatory effect (Berdugo et al 2021 ). Therefore, the use of a lower effective dose of glibenclamide could be a promising therapeutic strategy in the management of SARS-CoV-2-induced neuroinflammation even in non-diabetic patients.…”
Section: Introductionmentioning
confidence: 99%